A BREAKTHROUGH VARICELLA: WILL A NEW VACCINATION SCHEDULE CHANGE THE SITUATION? - E.A. Vishneva; L.S. Namazova-Baranova (Педиатрическая фармакология)
Varicella — is a common viral infection that can cause complications and adverse outcome not only in children at risk, but also in healthy children and adults. Socio-economic burden of disease due to both-direct health care, costs — to seek medical care and treatment,  and indirect — social. The introduction of immunization after the development of live attenuated vaccine has shown impressive results provided high coverage of morbidity and mortality associated with chickenpox declined sharply. However, the development of infection in vaccinated patients — a breakthrough varicella may be related with the deterioration of post-vaccinal immunity with time,  and the primary tolerance and inability to induce an effective immune response. Despite the undeniable progress in the prevention of chicken pox since the early 2000s. the world’s a discussion about the need to move to the two-dose vaccination scheme in national immunization programs has been started. Key words: vaccination, children, chickenpox, varicella, breakout. (Pediatric pharmacology. — 2011; 8 (6): 18–22).